DIPLOMASI PUBLIK KOREA SELATAN TERHADAP INDONESIA - Angga Nurdin Rahmat (Universitas Jenderal Ahmad Yani, 2018)
In the last decade South Korea has brought dominance in entertainment industry the youth generation in Indonesia. This condition is not only used for economic purpose but also includes various other interest and achievement. Referring to these problem, this research attempts to analyze what South Korea wants to achieves by using popular cultural instruments in Indonesia. This research will use the achievement of the public diplomacy by Mark Leonard associated with the purpose of introduction, positive appreciation, strengthen relationship and influencing. This research conducting by qualitative method with conduct interviews technique of respondents from the youth in Bandung.